The Role of Investment-Based Islamic Crowdfunding for Halal MSMEs: Evidence from Indonesia - Zaki Abdullah; Akhmad Akbar Susamto (Faculty of Shariah and Law, UIN Syarif Hidayatullah Jakarta, 2019)
Investment-based crowdfunding can be used as an alternative financing tool for Micro, Small and Medium Enterprises in Indonesia. Since the population in Indonesia is dominated by Muslim, Islamic financial technology companies that provide crowdfunding services are continue to emerge and develop. The development of these services also encourages the progress of the halal industry because both have integrated relationships. However, not all funding campaigns for crowdfunding services are successful. This study aims to analyze the development of Islamic crowdfunding business in Indonesia and factors affecting the success of funding campaigns in these services using multiple linear regression methods. Primary data obtained through interviews and literature review while secondary data is collected from 39 funding campaigns in 4 Islamic crowdfunding online services. It was found that the regulation of Islamic financial technology did not yet exist though in practice it was already widely found. On the other hand, crowdfunding models in Indonesia still need improvement in its scheme. By using a quantitative approach, it was found that funding target, campaign duration, payback periods and rate of return have a positive effect on campaign success, while a minimum amount of investment has a negative effect which means the minimum amount of investment available in the crowdfunding service is appropriate. After conducting research with a qualitative and quantitative approach, SWOT analysis was conducted at the end of the study to find out the challenges and opportunities for the halal industry in utilizing such Islamic crowdfunding service.